2015
DOI: 10.1182/blood-2015-03-631572
|View full text |Cite
|
Sign up to set email alerts
|

Identification and characterization of VEGF-A–responsive neutrophils expressing CD49d, VEGFR1, and CXCR4 in mice and humans

Abstract: Key Points Circulating CD49d+VEGFR1highCXCR4high neutrophils that stimulate angiogenesis at sites of hypoxia were identified in mice and humans. This subset was recruited to tissue by VEGF-A in a VEGFR1- and VEGFR2-dependent manner, and anti-CD49d therapy inhibited their extravasation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
174
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 199 publications
(191 citation statements)
references
References 50 publications
4
174
0
2
Order By: Relevance
“…VEGFR1 is present on monocytes, macrophages, and neutrophils and mediates their migration along VEGF gradients in vitro and their recruitment into ischemic tissue in vivo (42,43,50,51). Our data indicate that VEGFR1 contributes to leukocyte recruitment into the retinal vasculature when retinal levels of VEGF are high.…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…VEGFR1 is present on monocytes, macrophages, and neutrophils and mediates their migration along VEGF gradients in vitro and their recruitment into ischemic tissue in vivo (42,43,50,51). Our data indicate that VEGFR1 contributes to leukocyte recruitment into the retinal vasculature when retinal levels of VEGF are high.…”
Section: Discussionmentioning
confidence: 68%
“…VEGFR1 has been demonstrated on monocytes, macrophages, and neutrophils and mediates VEGF-stimulated leukocyte migration (42,43). To determine if VEGFR1 on leukocytes contributes to VEGF-induced retinal leukostasis, mice were given an intravenous injection of 100 μg rat anti-mouse VEGFR1 or rat IgG and an intraocular injection of 200 ng VEGF, and, after 24 hours, they were perfused with FITC-labeled Con A. Rho/VEGF-transgenic mice of different ages, day 16, day 20, day 30, 7 months, 12 months, or 15 months, or normal wild-type mice at 5 weeks (N-5wk) or 8 months of age (N-mo8) were perfused with rhodamine-labeled Con A.…”
Section: Figure 3 Turning Off Vegf Expression or Injection Of A Vegfmentioning
confidence: 99%
“…28,29 Comparing the numbers of neutrophils that infiltrated ischemic skeletal muscle 1 and 3 days after femoral artery ligation revealed that despite increased neutrophil infiltration in ischemic AMPKα2 ΔMC hindlimbs after 24 hours, the situation was reversed after 72 hours. These observations indicated that neutrophil survival was attenuated in the absence of the AMPKα2 subunit.…”
Section: Discussionmentioning
confidence: 99%
“…It should be noted that there is considerable variability in CD177 expression within the population and it is not expressed by all individuals 45 . Pro-angiogenic neutrophils that are CD49d + VEGR1 hi CXCR4 hi are also present in low quantities in both mouse and human blood and are recruited in response to VEGF-A 46, 47 . Aged neutrophils and neutrophils that have undergone reverse transmigration also display changes in their cell surface markers 1, 48 .…”
Section: Neutrophil Heterogeneity and Plasticitymentioning
confidence: 99%